2020
DOI: 10.1161/circulationaha.120.047077
|View full text |Cite|
|
Sign up to set email alerts
|

Dapagliflozin and Diuretic Use in Patients With Heart Failure and Reduced Ejection Fraction in DAPA-HF

Abstract: Background: In the DAPA-HF trial, the SGLT2 inhibitor dapagliflozin reduced the risk of worsening heart failure and death in patients with heart failure and reduced ejection fraction. We examined efficacy and tolerability of dapagliflozin in relation to background diuretic treatment and change in diuretic therapy following randomization to dapagliflozin or placebo. Methods: We examined the effects of study treatment in the following subgroups: no diuret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 24 publications
8
121
0
3
Order By: Relevance
“…These observations are similar to those reported with dapagliflozin in heart failure and a reduced ejection fraction, where the SGLT2 inhibitor also reduced the need for intensification of diuretic therapy, but had minimal effects on the average dose of prescribed diuretics over the course of double-blind treatment. 25 Importantly, when all outpatient and inpatient worsening events are considered together, the risk of a worsening heart failure event per 100 patient-years of follow-up was nearly 50, indicating that only half of our patients with chronic heart failure maintained clinical stability when followed for 1 year, even though our cohort comprised patients with primarily class II symptoms at the start of follow-up (Table).…”
Section: Discussionmentioning
confidence: 98%
“…These observations are similar to those reported with dapagliflozin in heart failure and a reduced ejection fraction, where the SGLT2 inhibitor also reduced the need for intensification of diuretic therapy, but had minimal effects on the average dose of prescribed diuretics over the course of double-blind treatment. 25 Importantly, when all outpatient and inpatient worsening events are considered together, the risk of a worsening heart failure event per 100 patient-years of follow-up was nearly 50, indicating that only half of our patients with chronic heart failure maintained clinical stability when followed for 1 year, even though our cohort comprised patients with primarily class II symptoms at the start of follow-up (Table).…”
Section: Discussionmentioning
confidence: 98%
“…In two recently completed studies—DAPA‐HF (Study to Evaluate the Effect of Dapagliflozin on the Incidence of Worsening Heart Failure or Cardiovascular Death in Patients With Chronic Heart Failure) and EMPEROR‐Reduced (EMPagliflozin outcomE tRial in Patients With chrOnic heaRt Failure With Reduced Ejection Fraction)—dapagliflozin and empagliflozin, respectively, reduced the risk of cardiovascular death and HHF by 26% in patients with HFrEF 20–22 . Importantly, these benefits were observed consistently in those with and without type 2 diabetes, were in addition to excellent background heart failure therapies, and resulted in an improvement in patient reported quality of life indices 20–32 . Because both trials recruited patients with chronic ambulatory HFrEF [and excluded patients with hospitalization due to decompensated heart failure less than 4 weeks prior to enrolment (DAPA‐HF)], it can be argued that the question of in‐hospital initiation of SGLT2 inhibitors during a WHF event has remained unanswered.…”
Section: Figurementioning
confidence: 99%
“…Conversely, as the diuretic effect of SGLT2i is modest, they might add trivial diuretic effects to loop diuretics. Analyses the benefits of dapagliflozin in DAPA-HF study revealed that such a diuretic effect was irrespective of use of background diuretic therapy or dose of diuretic therapy [ 159 ]. In sum, the clinicians should pay attention in the DM patients with concomitantly use of diuretics and SGLT2i.…”
Section: Effects Of Sglt2i On Clinical Parameters and Outcomes In mentioning
confidence: 99%